2013
DOI: 10.2355/isijinternational.53.1062
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Entry Behavior into Iron and Steel under Atmospheric Corrosion

Abstract: Electrochemical hydrogen permeation tests of pure Fe sheets rusted by cyclic corrosion test (CCT) and atmospheric exposure were carried out under controlled temperature and humidity to investigate the influence of atmospheric corrosion on the hydrogen entry behavior. The hydrogen entry into the Fe specimens rusted by CCT increased under wet condition, and the hydrogen entry was increased with the CCT cycle number. During drying process after the wetting, hydrogen entry was further enhanced and a peak of hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…At this time, on the surface of the steels, hydrogen evolution reaction can be evolved as one of the cathodic reactions. According to the reports by some researchers, [1][2][3][4][5] in atmospheric corrosion, H atoms can be absorbed into steels during the corrosion in the atmospheric environments. For example, if the concentration of absorbed H atoms reaches in the order of sub ppm, 1 000 MPa-class steels may be susceptible to hydrogen embrittlement.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, on the surface of the steels, hydrogen evolution reaction can be evolved as one of the cathodic reactions. According to the reports by some researchers, [1][2][3][4][5] in atmospheric corrosion, H atoms can be absorbed into steels during the corrosion in the atmospheric environments. For example, if the concentration of absorbed H atoms reaches in the order of sub ppm, 1 000 MPa-class steels may be susceptible to hydrogen embrittlement.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure test was started in our previous study. 27) Although the 2-month-exposed specimen in our previous study showed discernible increase of hydrogen permeation current density under wet condition and under the following drying process, 27) the 2-year-exposed specimen showed no clear change in hydrogen permeation current density as shown in Fig. 6, except for a slight increase at the beginning of the drying process after the wet condition.…”
Section: Echpt Of the Exposed Specimens Under Controlled Temperature mentioning
confidence: 67%
“…The current peak looks similar to the first peak of the specimen exposed at Chongqing for 6 months that appeared during drying process. In our previous study, 27) specimens exposed at Okinawa for 2 months showed slight Fig. 2.…”
Section: Echpt Of the Exposed Specimens Under Controlled Temperature mentioning
confidence: 70%
See 2 more Smart Citations